2003
DOI: 10.3177/jnsv.49.340
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipase Activities by Citrus Pectin

Abstract: SummaryThe oral administration of pectin to rats reduced and delayed the peak plasma triacylglycerol concentration. Pectin inhibited the hydrolysis of trioleoylglycerol emulsified with soybean phosphatidylcholine by pancreatic, carboxylester, and lingual lipases in a con centration-dependent manner. However, the effective concentration of pectin for lingual lipase was 100 times lower than that for pancreatic lipase. Pectin did not inhibit the tribu tyrin and p-nitrophenylbutyrate-hydrolyzing activities by panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…For this reason, there has been considerable interest in the development of effective strategies to reduce the caloric content of foods, or to reduce the spike in blood lipids that occurs after consuming a fatty meal. Several studies have suggested that certain types of dietary fibers can inhibit the digestion and absorption of lipids (Beysseriat, Decker, & McClements, 2006;Edashige, Murakami, & Tsujita, 2008;Tsujita et al, 2003;Yonekura & Nagao, 2009). Numerous physicochemical and physiological mechanisms may contribute to this effect, including the ability of dietary fibers to alter the rheology of the gastrointestinal fluids, to bind digestive components (such as bile salts and digestive enzymes), to alter the aggregation state of lipid droplets, to form protective coatings around lipid droplets, and to be fermented within the large intestine by colonic bacteria (Grabitske & Slavin, 2009;Lattimer & Haub, 2010;McClements, Decker, & Park, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there has been considerable interest in the development of effective strategies to reduce the caloric content of foods, or to reduce the spike in blood lipids that occurs after consuming a fatty meal. Several studies have suggested that certain types of dietary fibers can inhibit the digestion and absorption of lipids (Beysseriat, Decker, & McClements, 2006;Edashige, Murakami, & Tsujita, 2008;Tsujita et al, 2003;Yonekura & Nagao, 2009). Numerous physicochemical and physiological mechanisms may contribute to this effect, including the ability of dietary fibers to alter the rheology of the gastrointestinal fluids, to bind digestive components (such as bile salts and digestive enzymes), to alter the aggregation state of lipid droplets, to form protective coatings around lipid droplets, and to be fermented within the large intestine by colonic bacteria (Grabitske & Slavin, 2009;Lattimer & Haub, 2010;McClements, Decker, & Park, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, low-molecularweight fractions from commercial citrus pectin [in particular, molecular weight (M.W. ): 90,000] have been shown to associate with substrates and inhibit pancreatic lipase activity ( 16 ). Therefore, studies with appropriate pectin will clarify the cause of their dietary effects.…”
mentioning
confidence: 99%
“…Chitinchitosan and citrus pectin are both high molecular weight lipase inhibitors (19,20). However, both of these inhibitors are poorly soluble in water.…”
Section: Discussionmentioning
confidence: 99%
“…As pancreatic lipase inhibitors prevent postprandial hyperlipidemia (20)(21)(22)(23), PEE may also have prevented postprandial hyperlipidemia through low intestinal absorption of dietary fat by inhibiting pancreatic lipase. To examine this possibility, we determined the plasma TG levels after oral administration of corn oil with or without PEE to mice.…”
Section: Discussionmentioning
confidence: 99%